Efficient tumor regression by adoptively transferred CEA-specific CAR-T cells associated with symptoms of mild cytokine release syndrome. (1st September 2016) - Wang, Linan; Ma, Ning; Okamoto, Sachiko; Amaishi, Yasunori; Sato, Eiichi; Seo, Naohiro; Mineno, Junichi; Takesako, Kazutoh; Kato, Takuma; Shiku, Hiroshi
ABSTRACT: Carcinoembryonic antigen (CEA) is a cell surface antigen highly expressed in various cancer cell types and in healthy tissues. It has the potential to be a target for chimeric antigen receptor (CAR)-modified T-cell therapy; however, the safety of this approach in terms of on-target/off-tumor effects needs to be determined. To address this issue in a clinically relevant model, we used a mouse model in which the T cells expressing CEA-specific CAR were transferred into tumor-bearing CEA-transgenic (Tg) mice that physiologically expressed CEA as a self-antigen. The adoptive transfer in conjunction with lymphodepleting and myeloablative preconditioning mediated significant tumor regression but caused weight loss in CEA-Tg, but not in wild-type mice. The weight loss was not associated with overt inflammation in the CEA-expressing gastrointestinal tract but was associated with malnutrition, reflected in elevated systemic levels of cytokines linked to anorexia, which could be controlled by the administration of an anti-IL-6 receptor monoclonal antibody without compromising efficacy. The apparent relationship between lymphodepleting and myeloablative preconditioning, efficacy, and off-tumor toxicity of CAR-T cells would necessitate the development of CEA-specific CAR-T cells with improved signaling domains that require less stringent preconditioning for their efficacy. Taken together, these results suggest that CEA-specific CAR-based adoptive T-cell therapy may be effective for patients with CEA + solid tumors. Distinguishing the fine line between therapeutic efficacy and off-tumor toxicity would involve further modifications of CAR-T cells and preconditioning regimens.